1998
DOI: 10.1161/01.cir.98.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Production by the Heart

Abstract: Background —Beneficial effects of ACE inhibitors on the heart may be mediated by decreased cardiac angiotensin II (Ang II) production. Methods and Results —To determine whether cardiac Ang I and Ang II are produced in situ or derived from the circulation, we infused 125 I-labeled Ang I or II into pigs (25 to 30 kg) and measured 125 I-Ang I and II as well as endogenous Ang I and II in cardiac tissue and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Ventricles were immediately frozen in liquid nitrogen. Angiotensin peptides were extracted from plasma and tissue (13,20) and assayed for Ang II or fsAng II by radioimmunoassay (21). The antiserum displayed 75-85% cross-reactivity with fsAng II and 100% with the Ang II metabo-lites Ang III and Ang IV (Ang-(2-8) and Ang-(3-8), respectively).…”
Section: Construction Of Expression Vectors and Production Of Transgenicmentioning
confidence: 99%
See 2 more Smart Citations
“…Ventricles were immediately frozen in liquid nitrogen. Angiotensin peptides were extracted from plasma and tissue (13,20) and assayed for Ang II or fsAng II by radioimmunoassay (21). The antiserum displayed 75-85% cross-reactivity with fsAng II and 100% with the Ang II metabo-lites Ang III and Ang IV (Ang-(2-8) and Ang-(3-8), respectively).…”
Section: Construction Of Expression Vectors and Production Of Transgenicmentioning
confidence: 99%
“…The antiserum displayed 75-85% cross-reactivity with fsAng II and 100% with the Ang II metabo-lites Ang III and Ang IV (Ang-(2-8) and Ang-(3-8), respectively). Active plasma renin concentration was determined in plasma using an enzyme kinetic assay for Ang I generation in the presence of excess sheep renin substrate (20).…”
Section: Construction Of Expression Vectors and Production Of Transgenicmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In animal models it has been shown that despite adequate ACE inhibition there is still near normal production of angiotensin II, via ACE independent pathways, within the myocardium. 15 It was therefore postulated that block of the renin-angiotensin system at the angiotensin II type 1 receptor level would be more beneficial than ACE inhibition. In a metaanalysis of 17 trials looking at ARB the results showed that when ARB were compared with placebo there was a non-significant trend towards improved survival (p = 0.19) and decreased hospitalisation (p = 0.33) with ARB treatment.…”
Section: Medical Treatmentsmentioning
confidence: 99%
“…Most cardiac Ang II results from the conversion of local, rather than circulatory Ang I. 10 The cardiac RAS can regulate Ang II within the heart independently of the systemic RAS.…”
Section: The Heartmentioning
confidence: 99%